Development of Geogebra Assisted Learning Modules to Improve Mathematical Representation Abilities and Self Regulated Learning of Senior High School - Mayasari, Fitria; Napitupulu, E. Elvis; Sinaga, Bornok (Universitas Wiralodra, 2024)
This research aims to analyze: 1) Validity of the geogebra-assisted learning module developed; 2) Practicality of the geogebra-assisted learning module developed; 3) Effectiveness of the geogebra-assisted learning module developed; 4) Increasing mathematical representation abilities by using the geogebra-assisted learning modules that were developed; 5) Increasing self regulated learning by using the geogebra-assisted learning modules that were developed. This research is development research using the ADDIE development model. Winsgoal adalah slot mahjong gacor dengan fitur scatter hitam winrate kemenangan tinggi. Daftar dan nikmati fitur situs jackpot terbesar hari ini! This development model consists of 5 development stages, namely analysis, design, development, implementation and evaluation. From the results of trial I and trial II it was obtained: 1) The geogebra-assisted learning module developed meets the valid criteria; 2) The geogebra-assisted learning module developed meets the practical criteria; 3) The geogebra-assisted learning module developed meets the effective criteria; 4) The mathematical representation ability using the geogebra-assisted learning module that has been developed has increased as seen from the N-gain value of 0,45, meaning it is in the